Using the Inverse Three-Point Bending Test to Determine Mechanical Properties of Plant Stems - Alexander Anisimov; Maksim Suslov; Anna Petrova; Tatyana Chernova; Oleg Gorshkov; Tatyana Gorshkova (Methods and Protocols)
Biomechanical parameters of plant tissues and organs are increasingly recognized as key factors in plant development and application, increasing the demand for convenient devices for their study. The paper presents an original device for performing a three-point bending test using the inverse method, which is a modification of the classical (straight) three-point test. The designed device was tested in experiments to determine the modulus of elasticity of flax plant stems, and the results were compared with data obtained using the vibration method and the straight three-point bending test on a commercial instrument. Due to the high sensitivity associated with its design features, the device for the inverse three-point bending test is characterized by being able to adequately measure elastic moduli in plant stems over a wide range of values, from tens of MPa to tens of GPa. It also allows checking the effect of humidity, temperature, and water content on the mechanical properties of samples and is equipped with an automation system. The proposed device is quite affordable and can be effectively used both for young stem parts, whose mechanical properties are based on a hydroskeleton, and for mature, poorly hydrated parts with cell walls highly developed in sclerenchymatous tissues.